Penerapan Algoritma K-Means untuk Pemetaan Kebutuhan Obat Sesuai Prioritas dalam Pengadaan - Azizah, Laili Nur; Utari, Lis; Ningrum, Leny Tritanto; Rahmiyati, Dwi (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
ABSTRACTEach Ministry/Institution that has a primary clinic has its own budget allocation to support the operational activities of the primary clinic health service. The budget is usually adjusted to the size of the organization and the needs of its employees. One of the budgets is for spending on medical supplies. It is expected that the Primary Clinic, which is within the Ministries or Institutions, can provide health services according to the standards and needs of the scope they serve in accordance with budget availability. For this reason, so that the available budget can be optimized according to existing needs and is right on target, it is necessary to have a careful drug procurement plan. Segmentation/mapping of drug use is said to be important to determine the priority level of drug needs and can be used as a reference in drug procurement. The priority scale of needs in drug procurement is a process for mapping the types of drugs based on their needs by considering the drugs needed and the available budget, to avoid buying drugs that are not needed by the employees. Ideally, the types of drugs with high use are groups of drugs which procurement needs to be prioritized with the aim of ensuring the availability of these drugs. This study uses drug use data for 1 (one) semester, namely January to June 2022, using total usage and number of transactions using the clustering method with the K-Means algorithm. The results of drug mapping resulted in 197 drugs with low priority, 13 drugs with medium priority and 3 drugs with high priority. The results of the clustering results evaluation test show the value of the silhouette coefficient results is 0.8630 or "strong structure